Usability Analysis on Health Tracking Application using User Experience Questionnaire in Jakarta Area - Richard Richard; Aditya Kusumadwiputra; Adela Zahwa Firdaus Suherman (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
The study aims to investigate user satisfaction with the Health Tracking application in Jakarta, which is a vital tool used by the government to monitor the health of Indonesians. The research will employ a User Experience Questionnaire to gather feedback from a minimum of 400 respondents who are users of the Health Tracking application selected through random sampling. The analysis of the survey results will evaluate the User Interface (UI) and User Experience (UX) of the application and provide valuable insights that can be used to enhance the app's future development. The UEQ Data Analysis Tool will be utilized to analyze data. Based on the findings, it can be concluded that users are highly satisfied with the Health Tracking application's UI/UX. However, improvements can be made to enhance the perspicuity aspect of the app, along with maintaining or improving other factors. The results of this study can serve as a benchmark for the future development of the Health Tracking application.